β-Catenin–Histone Deacetylase Interactions Regulate the Transition of LEF1 from a Transcriptional Repressor to an Activator - Billin, Andrew N. (American Society for Microbiology, 2000)
Recent evidence suggests that certain LEF/TCF family members act as repressors in the absence of Wnt signaling. We show here that repression by LEF1 requires histone deacetylase (HDAC) activity. Further, LEF1 associates in vivo with HDAC1, and transcription of a model LEF1-dependent target gene is modulated by the ratio of HDAC1 to β-catenin, implying that repression by LEF1 is mediated by promoter-targeted HDAC. Consistent with this hypothesis, under repression conditions the promoter region of a LEF1 target gene is hypoacetylated. By contrast, when the reporter is activated, its promoter becomes hyperacetylated. Coexpression of β-catenin with LEF1 and HDAC1 results in the formation of a β-catenin/HDAC1 complex. Surprisingly, the enzymatic activity of HDAC1 associated with β-catenin is attenuated. Together, these findings imply that activation of LEF1-dependent genes by β-catenin involves a two-step mechanism. First, HDAC1 is dissociated from LEF1 and its enzymatic activity is attenuated. This first step yields a promoter that is inactive but poised for activation. Second, once HDAC1-dependent repression has been overridden, β-catenin binds LEF1 and the β-catenin–LEF1 complex is competent to activate the expression of downstream target genes.